2017
DOI: 10.1126/science.aao3691
|View full text |Cite
|
Sign up to set email alerts
|

Selective increase in CO 2 electroreduction activity at grain-boundary surface terminations

Abstract: Altering a material's catalytic properties requires identifying structural features that give rise to active surfaces. Grain boundaries create strained regions in polycrystalline materials by stabilizing dislocations and may provide a way to create high-energy surfaces for catalysis that are kinetically trapped. Although grain-boundary density has previously been correlated with catalytic activity for some reactions, direct evidence that grain boundaries create surfaces with enhanced activity is lacking. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
580
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(604 citation statements)
references
References 61 publications
(64 reference statements)
18
580
0
6
Order By: Relevance
“…[11] Although numerous materials, including nanostructured metals (for example,A u [12,13] and Ag [14,15] ), oxides (CuO [8] /Cu 2 O, [16] and ZnO [17] ), and chalcogenides (WSe 2 [18] /MoSe 2 , [19] and Ag 2 S [20] )h ave previously been used to promote CO 2 RR with enhanced performance toward various desired fuels,Sn-based materials are potentially more selective for HCOOH formation through tuning the particle size,m orphology,a nd composition. [25,26] Kanansgroup has studied the GB effect for CO 2 RR toward CO formation on flat, polycrystalline Au wires,with large grain size of about 200 mm. [25,26] Kanansgroup has studied the GB effect for CO 2 RR toward CO formation on flat, polycrystalline Au wires,with large grain size of about 200 mm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Although numerous materials, including nanostructured metals (for example,A u [12,13] and Ag [14,15] ), oxides (CuO [8] /Cu 2 O, [16] and ZnO [17] ), and chalcogenides (WSe 2 [18] /MoSe 2 , [19] and Ag 2 S [20] )h ave previously been used to promote CO 2 RR with enhanced performance toward various desired fuels,Sn-based materials are potentially more selective for HCOOH formation through tuning the particle size,m orphology,a nd composition. [25,26] Kanansgroup has studied the GB effect for CO 2 RR toward CO formation on flat, polycrystalline Au wires,with large grain size of about 200 mm. [25,26] Kanansgroup has studied the GB effect for CO 2 RR toward CO formation on flat, polycrystalline Au wires,with large grain size of about 200 mm.…”
mentioning
confidence: 99%
“…[21][22][23][24] Besides,c omputational studies have suggested that the broken local spatial symmetry adjacent to the grain boundary (GB) can alter the binding energies of reaction intermediates,and consequently accelerate CO 2 RR toward CO formation. [26] However,i ts till remains very challenging to explicitly clarify the correlation between GBs and the enhanced reactivity in nanostructured materials with small dimension (for example,b elow 10 nm). [26] However,i ts till remains very challenging to explicitly clarify the correlation between GBs and the enhanced reactivity in nanostructured materials with small dimension (for example,b elow 10 nm).…”
mentioning
confidence: 99%
“…CO part current density shows largest for AuCe‐47.3 (Figure c), which is 2.5 fold higher than that of AuCe‐33.2 at −0.6 V. The B doping is rather low, which is less than 0.2 at% determined by ICP‐AES, so the B doping effect is excluded. To quantify the Ce 3+ effect, the CO FEs at −0.5 V (Figure d) are picked up to compare the activity, for Ce 3+ effect could be clearly quantified at a low overpotential to minimize the ordinary Au‐CeO x CO 2 ER activity . The CO FE is clearly enhanced monotonically as the Ce 3+ concentration increases, and the CO FE shows linear relation with Ce 3+ concentration.…”
mentioning
confidence: 99%
“…[20][21][22][23][24] Die besonderen Vorteile dieser Te chnik wurden jüngst am Beispiel des Materials MoS 2 [8,25] demonstriert. B. Fe 4.5 Ni 4.5 S 8 )g emittelt über die untersuchte Elektrodenoberfläche angegeben werden kann.…”
unclassified